Sperm Quality Assessment in Stallions: How to Choose Relevant Assays to Answer Clinical Questions - Sophie Egyptien; Stéfan Deleuze; Joy Ledeck; Jérôme Ponthier (Animals, 2023)
Stallion sperm analysis is indicated for infertility diagnosis, pre-sale expertise, production of fresh or frozen doses, and frozen straw quality control. Various collection methods are described, and numerous assays can be performed on semen. Determining an approach for each of these cases is challenging. This review aims to discuss how to obtain relevant clinical results, answering stallion owners’ concerns. Semen can be collected with an artificial vagina on a phantom or a mare, by electro-ejaculation under anesthesia, or after pharmacological induction. The collection method influences the semen volume and concentration, while the total sperm number depends on the testicular production and collection frequency. In the seminal plasma, acidity, pro-oxidant activity, and some enzymes have repercussions for the semen quality and its conservation. Moreover, non-sperm cells of seminal plasma may impact semen conservation. Motility analysis remains a core parameter, as it is associated with fresh or frozen dose fertility. Computer-assisted motility analyzers have improved repeatability, but the reproducibility between laboratories depends on the settings that are used. Morphology analysis showing spermatozoa defects is useful to understand production and maturation abnormalities. Staining of the spermatozoa is used to evaluate viability, but recent advances in flow cytometry and in fluorochromes enable an evaluation of multiple intracellular parameters. Spermatozoa protein expression already has clinical applications, for example, as a fertility and freezing ability predictor. At present, stallion semen analysis ranges from macroscopic evaluation to assessing spermatozoa proteins. However, clinically, all these data may not be relevant, and the lack of standardization may complicate their interpretation.